TRENDS IN RELIGIOUS WORSHIP - Chackalackal, Saju (Journal of Dharma, 2006)
If religion is a reality that epitomizes the Divine-human encounter in the human milieu, worship is one of those essential activities that accentuates the said encounter. Our life here on earth is full of encounters: humancosmic, human-human, and human-Divine. Interestingly, religion brings an integral and integrating dimension to all these encounters. It is believed that spontaneous involvement in worship presupposes and inspires a reciprocal relationship between/among all the parties involved, including the Divine. This activity, therefore, brings about an affirmation (or, a reaffirmation) of the worth of all concerned. Worship being a human activity, it is natural to religiously oriented persons and groups to evolve patterns of religious worship. These patterns, in turn, are expected to facilitate meaningful human existence, effective bonding of in-group members, and development of an all-inclusive religious consciousness against the background of many people subscribing to other substitutes, religious, secular, or superstitious.